An Analytical Study on the Common Type of Smokeless Tobacco Available in the Iranian Market - Farhadmollashahi, Leila (Int J High Risk Behav Addict, 2014)
BACKGROUND: The use of smokeless tobacco is considered as a risk factor for oral cancer. OBJECTIVES: The current study aimed to chemically analyze, separate and measure the existing substances in a type of chewing tobacco. MATERIALS AND METHODS: In the current descriptive study, the investigated sample was a type of smokeless tobacco, known as BT, manufactured in India. First steam distillation method and Clevenger machine were used to separate and extract the essential oil of the sample. The presence of the desired compounds was evaluated in the essential oil, using gas chromatography (GC) and then gas chromatography coupled to mass spectrometry (GC/MS) analysis. RESULTS: Based on the results obtained by the applied technique, the presence of carcinogenic compounds, N-nitrosomethyl-vinylamine (162 µg/g), N-nitrosonornicotine (6.3 µg/g), and Acetaldehyde (117 µg/g) was confirmed in the sample. CONCLUSIONS: Chemical analysis of the sample confirmed the existence of carcinogenic compounds.